Experimental approach to nasal septal cartilage regeneration with adipose tissue-derived stem cells and decellularized porcine septal cartilage - Kuhlmann, Constanze; Schenck, Thilo Ludwig; Tluczynski, Katharina; Aszodi, Attila; Metzger, Philipp; Giunta, Riccardo; Wiggenhauser, Paul Severin (Xenotransplantation, 2020)
Background: Cartilage shortage is a major problem in facial reconstructive surgery. Prior studies have shown that decellularized porcine nasal septal cartilage (DPNC) seeded with primary human nasal chondrocytes enabled cartilage regeneration and showed potential as a replacement material for nasal cartilage. Since adipose tissue-derived stem cells (ASCs) are easily accessible and almost abundantly available, they appear to be a promising alternative to limited chondrocytes making the combination of DPNC and ASCs a feasible approach towards clinical translation. Thus, this study was intended to investigate the interactions between ASCs and DPNC in an in vitro model. Methods: DPNCs were seeded and 3D-cultured with primary human ASCs that were priorly characterized with trilineage differentiation and flow cytometry. Cell vitality and proliferation were evaluated by Live-Dead, alamarBlue, and PicoGreen assays. Chondrogenic differentiation was examined by DMMB assay and cryosectioning-based histology. Cell invasion within DPNC was visualized and quantified by fluorescent histology (DAPI, Phalloidin). Results: ASCs showed good adherence to DPNC and Live-Dead assay proved their viability over 2 weeks. AlamarBlueassay showed an increase in metabolic activity compared to 2D cultures, and PicoGreen assay demonstrated an increase of cell number within DPNC over time. Biochemical assays and histology added evidence of chondrogenic differentiation of 3D-cultured ASCs under the influence of chondrogenic induction medium. Fluorescent image analysis showed a significant increase of cell-occupied areas of scaffolds over time (P <.05). Conclusions: DPNC scaffolds provided a suitable environment for ASCs that allowed good cell vitality, high proliferation, and chondrogenic differentiation. Thus, the use of ASCs and DPNC yields a promising alternative to the use of primary human chondrocytes. For facial cartilage tissue engineering, we regard ASCs as an attractive alternative to human nasal chondrocytes due to their better accessibility and availability. Further research will be necessary to determine long-term effects and in vivo outcomes of ASCs and DPNC in cartilage regeneration of the face.
CRIS-Team Scopus Importer:2020-12-25
Keywords: adipose tissue-derived stem cells; cartilage regeneration; decellularized porcine nasal cartilage; extracellular matrix; facial reconstruction